2013
DOI: 10.1111/geb.12069
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal gradients in phylogenetic relatedness of angiosperm trees in North America

Abstract: Aim To test two predictions of the phylogenetic niche conservatism hypothesis for the latitudinal diversity gradient: (1) species in colder regions tend to be more phylogenetically related to each other (i.e. greater phylogenetic clustering) than those in warmer regions, and (2) clades are younger in colder regions. Location North America. Methods Correlation analysis was used to relate richness, mean clade age and phylogenetic relatedness (measured as phylogenetic species variability and net relatedness index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
88
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 50 publications
18
88
7
Order By: Relevance
“…The floras in temperate coniferous broad-leaved mixed forests, subalpine coniferous forests, and the alpine shrublands and meadows were significantly phylogenetically clustered, whereas the floras in the evergreen broad-leaved forests had phylogenetically random structure. Our results and previous findings are in line with the phylogenetic niche conservatism hypothesis, which suggests that species in cold regions tend to be more phylogenetically related than those in warmer regions (Qian, Zhang, Zhang, & Wang, 2013). Closely related plant species have similar traits to survive in the harsh climate prevailing at high elevations, which could be one of the possible reasons for phylogenetic clustering in these regions (Li et al, 2014;Webb et al, 2002).…”
Section: Drivers Of Phylogenetic Structures Of Seed Plantssupporting
confidence: 91%
“…The floras in temperate coniferous broad-leaved mixed forests, subalpine coniferous forests, and the alpine shrublands and meadows were significantly phylogenetically clustered, whereas the floras in the evergreen broad-leaved forests had phylogenetically random structure. Our results and previous findings are in line with the phylogenetic niche conservatism hypothesis, which suggests that species in cold regions tend to be more phylogenetically related than those in warmer regions (Qian, Zhang, Zhang, & Wang, 2013). Closely related plant species have similar traits to survive in the harsh climate prevailing at high elevations, which could be one of the possible reasons for phylogenetic clustering in these regions (Li et al, 2014;Webb et al, 2002).…”
Section: Drivers Of Phylogenetic Structures Of Seed Plantssupporting
confidence: 91%
“…investigated variation in the phylogenetic signal in flowering phenology and similarly found that the phylogenetic signal tended to be higher towards the temperate regions. These observed latitudinal patterns could be explained by the phylogenetic niche conservatism hypothesis, which posits that plant species tend to be more phylogenetically clustered and individuals tend to be younger in colder regions26. Such phylogenetic clustering would render LCV to be more similar in communities at higher latitudes composed of more closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…We expected that environments with potentially more stressful ecological conditions, namely marked seasonality of precipitation and/or low soil fertility, would have the lowest phylogenetic diversity, because these may represent ecophysiological barriers that are difficult for many lineages to surmount evolutionarily (Anacker & Harrison, 2012;Miller et al, 2013;Qian et al, 2013). Both savannas and SDTF Figure 3 Variation in phylogenetic diversity, as evaluated by several metrics, across Amazonia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an additional hypothesis to the one above, based on substrate age, is that tree communities in areas of the Amazon with greater ecophysiological barriers to growth (i.e. potentially more stressful environments) will show the lowest phylogenetic diversity (Qian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%